Democracy the name is Rule of Law (International Journal of Food and Nutritional Sciences, 2019)
The Preamble of the Constitution of India declares proudly that "we the people of India"have solemnly resolved to Constitute India into a "Sovereign, Democratic ,Republic", asoriginally incorporated therein and insertion of two words therein.